2023
DOI: 10.1128/msystems.00994-22
|View full text |Cite
|
Sign up to set email alerts
|

Viral Community Structure and Potential Functions in the Dried-Out Aral Sea Basin Change along a Desiccation Gradient

Abstract: Environmental viruses have added a wealth of knowledge to ecological studies with the emergence of metagenomic technology and approaches. They are also becoming recognized as important genetic repositories that underpin the functioning of terrestrial ecosystems but have remain moslty unexplored. Using shotgun metagenome sequencing and bioinformatic tools, we found that the viral community structure was affected during natural revegetation in the dried-up Aral Sea area, a model habitat for investigating natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Furthermore, viruses can encode other AMGs that enhance the metabolism of corrosive microbes. In Rc, AMG cysH, which is involved in sulfur metabolism and has been extensively discovered in other environments, was identified [48, 49]. In our study, we identified AMGs potentially associated with the MIC.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, viruses can encode other AMGs that enhance the metabolism of corrosive microbes. In Rc, AMG cysH, which is involved in sulfur metabolism and has been extensively discovered in other environments, was identified [48, 49]. In our study, we identified AMGs potentially associated with the MIC.…”
Section: Discussionmentioning
confidence: 80%
“…Viruses can contribute to the genetic and phenotypic evolution of their hosts, raising their competitiveness and environmental adaptability through AMGs ( 30 ). In carbon-poor soils, viruses established an enhanced beneficial relationship with bacteria, reflected by the elevated total abundance of AMGs annotated as CAZyme genes ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Microbiome-based control concepts are an interesting alternative to current pesticides, fertilizers and disinfectants (Vandini et al 2014 ). Plant and environmental health are directly linked to human health which becomes clear from the unintended consequences of intense agriculture in the former Aral Sea region (Wicaksono et al 2023b ) and destructive mining practices in the Salares of the hyperarid Atacama Desert in Northern Chile (Bonelli and Dorador 2021 ). Another link between human health and the depleted plant microbiome, especially the “edible microbiome”, was already suggested in 2015, which needs further evaluation (Berg et al 2015 , Wicaksono et al 2023a ).…”
Section: The Plant Holobiont In the Anthropocene And Implications For...mentioning
confidence: 99%